Comments on “Acupuncture and Moxibustion in the Treatment of Gynecological Perioperative Anxiety: A Systematic Review and Meta-Analysis” [Letter] - Li PQ; Huang M; Shao XM (Journal of Pain Research)
Pei-qi Li,* Mei Huang,* Xiao-mei Shao The Third Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-mei Shao, The Third Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China, Email 13185097375@163.com